Occult stage IIIA-N2 patients have excellent overall survival with initial surgery - Kim, Min P. (J Thorac Dis, 2018)
BACKGROUND: Patients may be found to have stage IIIA-N2 at the final pathology after the initial surgery. We want to determine the survival rate in this unique group of patients. METHODS: We reviewed all patients who underwent surgical resection for lung cancer from 2000 to 2011 who had pathologic stage N2 without induction therapy. We determined the clinicopathologic characteristics and survival rate in this unique group of patients. RESULTS: A total of 101 patients met the inclusion criteria. The average age of the group was 65 years old with 53 (53%) females. The chest computed tomography (CT) scans showed 30 patients (30%) with mediastinal lymphadenopathy (>1 cm) and 13 (13%) with multistation disease. The positron emission tomography-computed tomography (PET-CT) showed 24 patients (24%) with N2 positive uptake. Invasive mediastinal staging prior to surgery occurred in 43 patients (43%). Eighty-four patients underwent a lobectomy (83%), 7 with bilobectomy (7%), and 10 with pneumonectomy (10%). The most common pathology was adenocarcinoma with 73 patients (72%) and the second most common was squamous cell carcinoma with 22 patients (22%). Most of the patients completed the adjuvant chemoradiation therapy (86%). The 5-year survival rate was 48% and the 10-year survival rate was 24%. CONCLUSIONS: Pathologic stage IIIA-N2 non-small cell lung cancer (NSCLC) is a heterogeneous disease process with a very small group of patients undergoing initial surgery. Patients with occult stage IIIA-N2 who undergo initial surgery have an excellent overall survival rate.